A comparison between verbal working memory and vocabulary in bilingual and monolingual South African school beginners: implications for bilingual language assessment. Issue 1 (2nd January 2016) - Cockcroft, Kate
Abstract : This study compared bilingual and monolingual school beginners on measures of simple and complex verbal working memory and receptive and expressive vocabulary. The aim was to determine whether the tests of working memory are fairer measures of language ability than the vocabulary tests for bilingual children when tested in their second language. Participants were 120 school beginners, comprising English first- (monolingual) and second-language (bilingual) speakers, matched for age, grade and socio-economic background. All were being educated in English. Results showed that (1) the monolinguals outperformed the bilinguals on both expressive and receptive vocabulary; (2) there were no significant differences between the language groups on any of the working memory tests, when receptive and expressive vocabulary both were and were not statistically controlled; and (3) from the working memory measures, Digit Span tasks were significantly associated with vocabulary for both language groups, while Non-word Recall and Counting Recall were only related to vocabulary for the monolinguals. The findings have theoretical and practical implications for the functioning of verbal working memory in bilinguals and the types of verbal working memory measures suitable for assessing the language abilities of bilingual children.